Wage developments in the Caribbean. - DOWNES, Andrew S. (1997)
Reviews the experience of Caribbean companies with new forms of compensation, which have been, in many cases, associated with the implementation of structural adjustment programmes. Shows that Barbados companies have used various forms of gainsharing schemes, while companies in other countries have had a limited experience with gainsharing schemes. Outlines the lessons learned from the Barbados experience.